2009
DOI: 10.1039/b900865a
|View full text |Cite
|
Sign up to set email alerts
|

Competition between cleavage and decarboxylation in photolysis of α-carboxy-2-nitrobenzyl protected cysteine derivatives

Abstract: Photolysis of model peptides containing alpha-carboxy-2-nitrobenzyl (CNB) or alpha-carboxy-4,5-dimethoxy-2-nitrobenzyl (CDMNB) protected cysteines in aqueous solution gives the expected 2-nitrobenzyl-type photocleavage and can be accompanied by photodecarboxylation depending on structural aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…The photolabile agarose is modified with α-carboxy-2-nitrobenzyl cysteine, similar to S-2-nitrobenzyl cysteine previously reported to afford photolabile functionality to agarose (Luo and Shoichet 2004). However, the α-carboxy-2-nitrobenzyl leaving group used in the present study has been shown to be less cytotoxic and more water soluble than that of the 2-nitrobenzyl moiety (Pan and Bayley 1997; Walker et al 1998; Kotzur et al 2009). A digital micromirror device (DMD) in our photolithography apparatus served as a dynamic mask for irradiating both PEG and the photolabile agarose.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The photolabile agarose is modified with α-carboxy-2-nitrobenzyl cysteine, similar to S-2-nitrobenzyl cysteine previously reported to afford photolabile functionality to agarose (Luo and Shoichet 2004). However, the α-carboxy-2-nitrobenzyl leaving group used in the present study has been shown to be less cytotoxic and more water soluble than that of the 2-nitrobenzyl moiety (Pan and Bayley 1997; Walker et al 1998; Kotzur et al 2009). A digital micromirror device (DMD) in our photolithography apparatus served as a dynamic mask for irradiating both PEG and the photolabile agarose.…”
Section: Introductionmentioning
confidence: 75%
“…Figure 1 outlines the synthesis pathway for the photolabile cysteine grafted to agarose. First, the photolabile moiety tert -butyl 2-bromo-2-(2-nitrophenyl)acetate ( t Bu-BNPA) was synthesized according to a modified protocol (Kotzur et al 2009). Briefly, 2-(2-nitrophenyl)acetic acid (5.0 g, 27.6 mmol), 4-dimethylaminopyridine (1.85 g, 15.1 mmol), and N , N ’diisopropylcarbodiimide (5.2 ml, 33.2 mmol) were dissolved in 50 ml dichloromethane (DCM) and cooled to 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…16 After illumination, the PG is cleaved and the caged biomolecule is released irreversibly, thus revealing the active species. Photocaged Cys has been site-specifically incorporated to study thiol function and targeted covalent labeling in small molecules, 17 peptides, 18 and proteins. 19 Photocaged selenocysteine has also been reported.…”
mentioning
confidence: 99%
“…[1] Such orthogonal and mild photolytic cleavage is particularly attractive for solid-supported organic synthesis, [2] in the field of combinatorial library screening, [3] and for the tracking of molecular dynamics in biological systems. [4] Of the myriad of photocleavable protecting groups which have been studied, the o-nitrobenzyl group is certainly the predominant one since it enables the caging of a wide range of functionalities, such as carboxy, [5] amine, [6] hydroxy, [7] and thiol. [8] In addition, the use of light as a trigger provides a straightforward means to obtain spatial and temporal control over a desired molecular cleavage, [9] which has found significant attention in constructing patterns of multiple cell lines, [10] the production of 3D structured materials for tissue scaffolds, [11] and the photo-caging of active compounds [12] for instance.…”
mentioning
confidence: 99%